2019
DOI: 10.1212/wnl.0000000000008393
|View full text |Cite|
|
Sign up to set email alerts
|

Self-management program improves participation in patients with neuromuscular disease

Abstract: ObjectiveTo investigate the effectiveness of Energetic, a self-management group program combining aerobic training, energy conservation management, and relapse prevention to improve social participation in patients with neuromuscular disease (NMD) and chronic fatigue.MethodsIn this multicenter, assessor-blinded, 2-armed randomized controlled trial with repeated measurements, 53 patients with various types of NMD and chronic fatigue were randomly allocated to Energetic, a 4-month group intervention, or to usual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 34 publications
0
31
0
Order By: Relevance
“…This requires behavioural and/or technological solutions including strategies like goal setting, self-monitoring, and feedback. However, few studies on exercise interventions among NMD have focused on the sustainability of acquired results of exercise programmes [23]. Based on other studies of chronic health conditions such as obesity [24] and heart failure [25], motivational interviewing (MI) seems to be a promising basis for implementation of a coaching programme in interventions to increase physical activity within the NMD population [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…This requires behavioural and/or technological solutions including strategies like goal setting, self-monitoring, and feedback. However, few studies on exercise interventions among NMD have focused on the sustainability of acquired results of exercise programmes [23]. Based on other studies of chronic health conditions such as obesity [24] and heart failure [25], motivational interviewing (MI) seems to be a promising basis for implementation of a coaching programme in interventions to increase physical activity within the NMD population [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…However, no significant result was observed in treatment with elamipretide (Karaa et al 2018) or inorganic nitrate (Nabben et al 2017). A study using energetic intervention (Veenhuizen et al 2019) showed improvement in social participation, motor function and mental condition after treatment. Another study with 10 weeks of AET (Siciliano et al 2012) showed a reduction of the increase of lactate during the exercise test and lower mean blood lipoperoxide level.…”
Section: Included and Excluded Studiesmentioning
confidence: 99%
“…However, there is still a lack of effective individual exercise planning for patients with different degrees of muscle weakness and personal preference of training pattern (Voet et al 2013). Veenhuizen et al (2019) carried out a multicenter assessor-blinded, two-arm randomized controlled trial to search for an effective plan of energetic intervention among 53 patients with neuromuscular disease, including five with facioscapulohumeral dystrophy, five with inclusion body myositis, 18 with MM, five with hereditary motor and sensory neuropathy, four with myasthenia gravis, three with myotonic dystrophy type 1, two with hereditary spastic paraplegia, one with chronic idiopathic axonal polyneuropathy, one with congenital myopathy, one with McArdle syndrome, two with congenital fiber type disproportion, one with limb girdle muscular dystrophy, one with autosomal dominant distal and anterior dystrophy, one with Kennedy syndrome, one with hyperkalemic periodic paralysis, two with Duchenne carriers and one with postpolio syndrome.…”
Section: Energetic Interventionmentioning
confidence: 99%
“…Considering this, physiotherapist's goal is to explain to patient the importance of adherence to the regime, the importance of prescribed techniques and strategies need to alleviate the dyspnoea, use of accessory muscles, and decrease incisional pain that can be achieved through patient education (Veenhuizen et al, 2019). To alleviate use of accessory muscle and to relax the diaphragm which leads to relaxation and decreased respiratory rate, Diaphragmatic breathing exercise in semi fowler's position should be done (2*10).…”
Section: Patient Educationmentioning
confidence: 99%